Vowels Reading Of Arabic Present Tense In Yaf’al Form For Lip And Coronal Articulation/ Pembacaan Vokal Pola Fiil Mudhori Yaf’al Bagi Artikulasi Bibir Dan Koronal - Mohamad Isa, Abdul Azim; Ismail, Zawawi; Jamali, Hairun Najuwah; Nordin, Fitri Nurul’ain (Ijaz Arabi Journal of Arabic Learning, 2021)
The Arabic vowel consists of three main vowels namely /a/ (fathah), the vowel /i/ (kasrah), and the vowel /u/ (dhammah). This study aims to analyze the vowels of the Arabic present tense in the pattern' af'al which is determined by the arrangement of letters. This study also aims to help read active verbs of yaf’al Arabic among Arabic language students who have difficulty determining the correct vowel of the three vowel fractions. In addition, this study can help linguists in general and Arabic in particular to determine the vowel reading of the letter 'ain (ع) on the active verb pattern of modern Arabic' af'al which is divided into vowels / a / (fathah), vowel /i/ (kasrah), and the vowel /u/ (dammah). This study uses a qualitative method. Samples of this study were taken from Al-Khalil dictionary as well as al-Ma'aniy online dictionary. Only three syllable active verbs are analyzed as the three syllable active verbs in Arabic will change to three different vowels when in the verb tense. The analysis is focused on the arrangement of the letters' ain (ع) in the past tense verb. Clearly, the study's findings have shown that the arrangement of 'ain (ع) on the active Arabic verb of the past affects the vowel on the 'ain (ع) active verb of the present Arabic. At the same time, this study provides an alternative that shows that the vowels at the letter 'ain (ع) of the active Arabic verb of the present time are non-random.